“What if They Are Pre-conception? What Should We Do?”: Knowledge, Practices, and Preferences for Safer Conception Among Women Living With HIV and Healthcare Providers in Gaborone, Botswana - Gutin, Sarah A.; Harper, Gary W.; Moshashane, Neo; Bitsang, Christina; Harries, Jane; Ramogola-Masire, Doreen; Morroni, Chelsea (Frontiers in Global Women's Health, 2020)
Safer conception interventions that address HIV care, treatment, and prevention for HIV-affected couples are increasingly available in sub-Saharan Africa. Botswana, an HIV endemic country, is yet to offer formal safer conception services although universal test-and-treat approaches mean that increasing numbers of young, sexually active people living with HIV will start treatment and likely desire childbearing. In order to advance the safer conception discussion in Botswana, it is necessary to understand the current safer conception knowledge, practices, and preferences of healthcare providers and women living with HIV (WLHIV). We conducted qualitative in-depth interviews with 10 HIV healthcare providers and 10 WLHIV in Gaborone. Interviews were analyzed using a phenomenological approach. Safer conception knowledge was limited and safer conception discussions were rare. Healthcare provider and WLHIV preferences were at odds, with providers preferring WLHIV to initiate safer conception discussions, and WLHIV desiring providers to initiate safer conception discussions. Quotes from women and providers highlight deeper issues about power dynamics, concerns about stigma among women, and provider fears about promoting pregnancy. Providers emphasized the need for guidelines and training in order to improve the provision of safer conception counseling. These findings point to areas where safer conception in Botswana can be improved. Both WLHIV and providers would benefit from having information about a range of safer conception methods and approaches. In addition, since WLHIV felt hesitant about initiating safer conception conversations and feared stigma, and because putting the onus for starting safer conception discussions on women is a reversal of normal roles and power structures, providers must take the lead and routinely initiate fertility desire and safer conception discussions. Assisting healthcare providers with clear safer conception guidelines and training would improve the provision of accurate safer conception counseling and facilitate reproductive choice.